Routine and adaptive expert strategies for resolving ICT mediated communication problems in the team setting. - Varpio L; Schryer CF; Lingard L (Medical Education, 2009)
CONTEXT: The use of information and communication technologies (ICTs) for supporting interprofessional communication is becoming increasingly common in health care. However, little research has explored how ICTs affect interprofessional communication, or how novices are trained to be effective interprofessional ICT users. This study explores the interprofessional communication strategies of nurses and doctors (trainees and experts) when their communications were mediated by a specific ICT: an electronic patient record (EPR). METHODS: A total of 72 doctors and nurses participated in this 8-month study on a paediatric in-patient ward. Eighty hours of non-participant observations and 20 semi-structured interviews were conducted. All data were rendered anonymous prior to analysis. Using a constructivist grounded theory approach, one researcher read and analysed all data recursively. As emergent themes were identified, exemplary portions of the data were discussed with three additional researchers to resolve discrepancies and confirm the coding structure. Expertise literatures informed the final analyses. RESULTS: Three interprofessional communication strategies were identified: (i) all participants routinely formulated 'workarounds' to circumvent problematic EPR-mediated communications; (ii) workarounds were classifiable as instances of Abandoning, Forcing or Submitting to the EPR, and (iii) novices learned workaround strategies through an informal curriculum, but they did not learn to manage the interprofessional effects of these workarounds. CONCLUSIONS: Trainees relied on workarounds as simplified routines, demonstrating routine expertise. Staff members, demonstrating adaptive expertise, used workarounds as part of a broader network of people and communication tools. Explicit training regarding this network and the ways in which workarounds conceal this network may help trainees develop adaptive expertise.